Daniel Buren - Buren, Daniel; Lisson Gallery, London; Crippa, Elena; Logsdail, Nicolas (London : Lisson Gallery, 2007)
Daniel Buren : engaging specificities / Claire Doherty ##Conversation between Daniel Buren & Pierre Huyghe ##Landscape : working within a social and historical context : [extract from an interview / with Hans Ulrich Obrist] ##Can art get down from its pedestal and rise to street level? / Daniel Buren.
Published on the occasion of 'Daniel Buren - New Situated Works' at Lisson Gallery, 18 May - 23 June 2007
boek
Keywords: Buren, Daniel